2022
DOI: 10.1021/acs.iecr.2c01297
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive Removal of Radioactive Cesium from Model Nuclear Wastewater over Hydroxyl-Functionalized Mxene Ti3C2Tx

Abstract: Selective removal of 137 Cs from nuclear wastewater is still a challenge due to the issues of efficient adsorbent exploitation and high concentrations of competitive ions. In this study, two-dimensionallayered Mxene Ti 3 C 2 T x achieved the surface alkaline modification with KOH to be used as an efficient adsorbent for Cs + removal from model wastewater. Hydroxyl-modified Ti 3 C 2 T x obtained improved the delamination morphology and surface structure compared with the pristine Ti 3 C 2 T x . In addition, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…It was clearly observed from Figure d–f that the binding energies of phenolic hydroxyl (CHOH) demonstrated obvious shifts (0.14–0.33 eV) after Cs adsorption onto HCP-HBAs, indicating the formation of –OCs . More importantly, the binding energies of −CH 2 OH also significantly shifted (0.41–0.73 eV), confirming that the hydroxymethyl group can boost the Cs adsorption.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…It was clearly observed from Figure d–f that the binding energies of phenolic hydroxyl (CHOH) demonstrated obvious shifts (0.14–0.33 eV) after Cs adsorption onto HCP-HBAs, indicating the formation of –OCs . More importantly, the binding energies of −CH 2 OH also significantly shifted (0.41–0.73 eV), confirming that the hydroxymethyl group can boost the Cs adsorption.…”
Section: Resultsmentioning
confidence: 74%
“…It was clearly observed from Figure 5d−5f that the binding energies of phenolic hydroxyl (�CHOH) demonstrated obvious shifts (0.14−0.33 eV) after Cs adsorption onto HCP-HBAs, indicating the formation of −OCs. 57 More importantly, the binding energies of −CH 2 OH also significantly shifted (0.41−0.73 eV), confirming that the hydroxymethyl group can boost the Cs adsorption. Combined with the results of 13 C CP/MAS NMR, FT-IR, XPS, and selectivity experiments, it can be speculated that the deprotonated phenolic hydroxyl groups were exchanged with Cs + , and the residual hydroxymethyl in the polymer backbone played the role of cooperative coordination, as illustrated in Figure 6.…”
Section: Adsorption Mechanismmentioning
confidence: 85%
“…[ 12 ] On the other hand, it is reported that the surface termination by −O and −OH can enhance the Sr 2+ capturing efficiency by forming stable bonding with radioisotopes. [ 13 ] Therefore, searching an alternative etchant, which is more efficient in radioisotope removal and ecofriendly than the conventional hazardous chemicals, is needed.…”
Section: Introductionmentioning
confidence: 99%
“…These radionuclides can cause severe health issues in human cells as well the ecosystem. Since MXenes are novel materials developed in recent years, very few studies have been reported on barium 9,10 and cesium 11,12 ion removal. In addition, none of these studies used radioactive isotopes.…”
mentioning
confidence: 99%